Management of pericardial disease - Herzog, Eyal (Springer International Publishing, 2014)
The clinical aspects of pericardial disease encompass acute and recurrent pericarditis, pericardial effusion and pericardial tamponade, constrictive pericarditis, and effusive-constrictive pericarditis. These disorders differ not only in clinical presentation but also in the timeline of development, thus management of pericardial disease can be challenging for many clinicians. To assist medical professionals with this often complex area, this book provides an extensive review of pericardial disease evaluation and management in a unified, stepwise pathway-based approach.   Management of Pericardial Disease contains a selection of defining clinical images to guide in identification and management of pericardial disease. Fellows, residents, cardiologists, thoracic medicine physicians, cardiothoracic surgeons, radiologists, and intensive care and emergency medicine physicians alike will find this book to be an essential resource for developing the skills and knowledge applicable to managing pericardial disease in patients.